Urgensi Perlindungan Hak dan Implementasi Pemberian Restitusi bagi Anak Korban Pelecehan Seksual - Viane Patricia; Hery Firmansyah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Cases of child sexual abuse have become a serious concern in various countries, including Indonesia. Children, as a vulnerable group, often become victims of sexual crimes, and the impact is not only on the physical aspect but also on their psychological well-being and overall development. Sexual abuse experienced by children can cause long-lasting trauma and affect their quality of life in the future. This research uses the normative legal research method, which relies on the study of library materials. Normative legal research is a type of research conducted through the examination of secondary data or library materials. Cases of child sexual abuse are one of the serious issues that need special attention within the legal system in Indonesia. Children, as a vulnerable group, often become victims of this crime, which not only leaves physical impacts but also deep and long-lasting psychological trauma. The urgency of this protection is not separate from the significant challenges faced in the Indonesian legal system, which still needs to be improved in providing guarantees of protection for child victims of sexual abuse.